Conflict in Ukraine – Legal Battlefield. Editorial - Grzebyk, Patrycja (Polish Review of International and European Law, 2024)
Article describes unprecedented (in terms of scope, time framework, arguments) legal actions undertaken by Ukraine in response to Russian aggression which began in 2014 and which escalated in 2022. In the framework of lawfare conducted by Ukraine, article focuses on the allegations of genocide which appeared on both sides of conflict. In consequences, it addresses the current proceeding in the International Court of Justice: Ukraine v. Russian Federation, with 32 States intervening, in which Ukraine attempts to prove that Russia started intervention under the pretext of genocide allegedly committed in Eastern Ukraine. At the same time, article presents arguments concerning the possibility of classification of crimes committed by Russia in Ukraine as genocide. At the end the article presents the content of the volume 2 of PRIEL of the year 2023.